2019
DOI: 10.1111/hsc.12750
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness—‘It will crumble men’: The views of staff and service users about facilitating the identification and support of people with an intellectual disability in homeless services

Abstract: People with an intellectual disability (ID) face significant health inequalities and barriers to accessing appropriate support, which are made worse if the person is also homeless. An important barrier is that services may not recognise that the person has ID. This qualitative study explored the views of staff members and service users about the identification and support needs of homeless people with ID and the role of an ID screening questionnaire as a way to help improve service provision. Semistructured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 18 publications
(26 reference statements)
1
25
0
Order By: Relevance
“…The ideal situation is to prevent people with ID from becoming homeless. For this to be realized, there needs to be nationally coordinated strategic policy approaches to homelessness and the inclusion of the specific needs of the ID population (McKenzie et al., 2019). In some studies, wider transcultural issues were identified as predetermining factors that may result in homelessness.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The ideal situation is to prevent people with ID from becoming homeless. For this to be realized, there needs to be nationally coordinated strategic policy approaches to homelessness and the inclusion of the specific needs of the ID population (McKenzie et al., 2019). In some studies, wider transcultural issues were identified as predetermining factors that may result in homelessness.…”
Section: Resultsmentioning
confidence: 99%
“…In order to provide pathways out of homelessness, appropriate and responsive physical and psychosocial interventions and supports need to be in place (van der Laan et al., 2018; van Straaten et al., 2017). A significant barrier that impacted upon the care and support provided to people with ID within homelessness services, and those exiting, related to the limited knowledge, skills and expertise of support staff regarding the specific needs and requirements of the population (McKenzie et al., 2019). To help mitigate against these factors, wider policies and strategies need to include a focus on the needs of people with ID to ensure that education opportunities, discrimination, social exclusion, socioeconomic disparities and equality of healthcare access provision are identified and resources and support targeted (Gowda et al., 2017; Nishio et al., 2017; van Straaten et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations